60.0k views
0 votes
5. 3x + 5y + 5z =1
x - 2y = 5
2x + 4y = 11

User Jaget
by
5.4k points

1 Answer

2 votes

Answer:

see explanation

Explanation:

Given the 3 equations

3x + 5y + 5z = 1 → (1)

x - 2y = 5 → (2)

2x + 4y = 11 → (3)

Use (2) and (3) to solve for x and y

Multiply (2) by 2

2x - 4y = 10 → (4)

Add (3) and (4) term by term

4x = 21 ( divide both sides by 4 )

x =
(21)/(4\\)

Substitute this value of x into (3)

2 ×
(21)/(4\\) + 4y = 11


(21)/(2\\) + 4y = 11 ( subtract
(21)/(2\\) from both sides )

4y =
(1)/(2) ( divide both sides by 4 )

y =
(1)/(8\\)

Substitute the values of x and y into (1) and solve for z

3 ×
(21)/(4\\) + 5 ×
(1)/(8\\) + 5z = 1


(63)/(4) +
(5)/(8) + 5z = 1


(131)/(8) + 5z = 1 ( subtract
(131)/(8) from both sides )

5z = -
(123)/(8) ( divide both sides by 5 )

z = -
(123)/(40)

Solution is

x =
(21)/(4\\), y =
(1)/(8\\), z = -
(123)/(40)

User Leevo
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.